The Effect of English Fun Camp Program in Public Speaking of STKIP Al Maksum Students - Sara Frimaulia; Reza Aulia Azmi (The Seall Journal, 2023)
The purpose of this study is to find out the influences of the English Fun Camp towards student’s speaking skill. The study was conducted by qualitative research methods. The participants of this study were 20 PTI students at STKIP AL Maksum Langkat. The research data was gathered by interview. In collecting the data, the interviewees were selected by using purposive sampling. The 20 selected participants had joined at English Fun Camp. The result showed that the English Fun Camp was able effect on public speaking. It can be seen from how they mastering a lot of vocabulary, pronunciation and fluency in speech, grammar and comprehension ability and establishing self-confidence. These components are interrelated to improve speaking skill for students, so the students can face the various challenges they worry about speaking. So based on the data, it can be concluded that English Fun Camp has a significant influence on enhancing students speaking skill and treat student’s confidence to be better keywords: english fun camp, public speaking